PENINGKATAN KETERAMPILAN MEMBACA LANCAR MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE TALKING STICK PADA PESERTA DIDIK DI KELAS II SD NEGERI 09 PASAMAN KABUPATEN PASAMAN BARAT - Sherlina Aulia; Elfia Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the fluent reading skills of grade II students of SD Negeri 09 Pasaman, West Pasaman Regency, which are still relatively low. This study aims to determine the application of Improving fluent reading skills using the Cooperative Learning Type Talking Stick learning model. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles. Each cycle has four stages, namely planning, implementation, observation, and reflection. The subjects of this research were teachers and students of class II totaling 30 people. The results of this study indicate that the teaching module in cycle I obtained a percentage of 87.5% with a Good qualification (B), and in cycle II increased to 98.83% with a Very Good qualification (SB). Teacher activity in cycle 1 obtained a percentage of 78.12% with a Good qualification (B), and increased in cycle II to 96.82% with a Very Good qualification (SB). Student learning activities in cycle I obtained a percentage of 78.12% with a Good qualification (B), and increased in cycle II to 96.82% with a Very Good qualification (SB). Student learning outcomes in knowledge assessment in cycle I with an average of 79.67 with a qualification (C), increased in cycle II with an average of 84.33 with a qualification (B). The learning outcomes of students' fluent reading skills assessment in cycle I with an average of 75.67 with qualification (C), increased in cycle II with an average of 84.67 with qualification (B). It can be concluded that the Talking Stick Type Cooperative Learning model can improve students' fluent reading skills in Indonesian language learning in grade II of elementary school.